Co-decorated tellurium nanotubes for energy storage applications - Bhol, Prangya; Swain, Swarnalata; Jena, Satyaranjan; Bhatte, Kushal; Rout, Chandra Sekhar; Saxena, Manav; Jadhav, Arvind H.; Samal, Akshaya K. (ACS Applied Nano Materials, 2021)
This paper explicitly discusses the synthesis of Co-decorated Te nanotubes (NTs) using Te NTs as the sacrificial template and the evaluation of their electrochemical performance. First, one-dimensional (1D) Te NTs were synthesized and characterized by spectroscopic and microscopic tools such as UV-visible spectroscopy, X-ray diffraction spectroscopy, X-ray photoelectron spectroscopy, field-emission scanning electron microscopy, high-resolution transmission electron microscopy, and energy-dispersive X-ray spectroscopy analyses. The as-prepared hexagonal Te NTs (h-Te NTs) possess diameters of about 35 +/- 5 nm and lengths of about 500 +/- 50 nm and were used for the synthesis of Co-decorated Te NTs. The 1D nanostructure with excellent conductivity enables the material to show excellent electrochemical performance. The asymmetric assembly of the CoTe-2//AC electrode material displayed a high specific capacitance of 147 F g(-1) (specific capacity, 162 C g(-1) at a current density of 2 A g(-1) in 4 M KOH electrolyte. In addition to that, the assembly of CoTe-2//AC achieved an excellent energy density of 51.1 W h kg(-1) at a power density of 2294 W kg(-1) and confirmed the as-synthesized Co-decorated Te NTs to be an excellent electrode material.
Keywords: cobalt; nanotubes; pseudocapacitors; surfactant; Tellurium; template